Resíduos orgânicos e fósforo como condicionantes de solo degradado e efeitos sobre o crescimento inicial de Dipteryx alata Vog. - Machado, Keila Da Silva [UNESP]; Maltoni, Kátia Luciene [UNESP]; Santos, Cinthia Montibeller; Cassiolato, Ana Maria Rodrigues (Universidade Federal de Santa Maria, 2014)
In northwestern São Paulo State, it was established, in 1965, the hydroelectric station of Ilha Solteira (CESP) that produced extensive degraded areas, from where it was removed the soil superficial layers. For the re-establishment of the vegetation, in areas like these, it is necessary the addition of chemical inputs and organic material. Associating the presence in the area of macrophytes, to the need of recovery of degraded areas and the availability of seeds from native species of Cerrado, it was intended the development of this work, with the objective of evaluating the addition effects of organic residue and phosphorus on the material of degraded soil and on the initial growth of Dipteryx alata, arboreal species of 'cerrado'. The soil material was collected in area of degraded soil by the construction of Ilha Solteira hydroelectric station. The experiment was conducted in two environmental conditions, greenhouse and plenty of sun. The treatments consisted of four phosphorus doses (0, 100, 200 and 300 mg dm-3 of P2O5), with or without macrophytes addition, with 16 treatments and 10 repetitions each one. The used macrophytes, collected at Jupiá hydroelectric station, in Mato Grosso do Sul state, were dried, sliced, incorporated to the soil material and incubated during 60 days. The seeds of Dipteryx alata, collected around of the area, were sowed in washed sand and after 60 days introduced in the treatments. The plants were appraised monthly for height, stem diameter and leaves chlorophyll. After 210 days, the plants were collected and evaluated for fresh and dry weight of aerial part and radicular system and the soil material was evaluated for fertility and microbial activity by the carbon of liberated CO2. The organic residue, incorporated to the material of soil degraded, positively affects the soil fertility and the soil microbial activity. The applied phosphorus doses influenced the behavior of Ca, SB, H+Al and CTC, when applied in the absence of organic residue, it promoted significant and linear increments for values of potential acidity, and indicated the organic residue importance. The initial growth of the Dipteryx alata was favored by the protected cultivation, for the incorporation of organic residue and for the phosphorus addition to the soil. At the end although the material of degraded soil comes as good perspective for disposal of this residue, studies about the field conditions are necessary.

Na região Noroeste do Estado de São Paulo, foi estabelecida, em 1965, a Usina Hidrelétrica de Ilha Solteira (CESP), que produziu extensas áreas degradadas, de onde foram retiradas as camadas superficiais do solo. Para o restabelecimento da vegetação, em áreas como estas, é necessária a adição de insumos químicos e matéria orgânica. Associando-se a presença na região de macrófitas à necessidade de recuperação de áreas degradadas e a disponibilidade de sementes de espécies nativas de cerrado, propôs-se o desenvolvimento deste trabalho, com o objetivo de avaliar os efeitos da adição de resíduo orgânico e fósforo sobre material de solo degradado e sobre o crescimento inicial de Dipteryx alata, espécie arbórea de cerrado. O material de solo foi coletado em área degradada pela construção da Usina Hidrelétrica de Ilha Solteira (SP). O experimento foi conduzido em dois ambientes, casa de vegetação e a pleno sol. Os tratamentos consistiram de quatro doses de fósforo (0, 100, 200 e 300 mg dm-3 de P2O5), com ou sem adição de macrófitas, produzindo 16 tratamentos com 10 repetições cada um. As macrófitas utilizadas, coletadas na Usina Hidrelétrica de Jupiá (MS), foram secas e passadas em picadeira, incorporadas ao material de solo e incubadas por 60 dias. As sementes de Dipteryx alata, coletadas nas proximidades da área, foram semeadas em areia lavada e após 60 dias introduzidas nos tratamentos. As plantas foram avaliadas mensalmente quanto à altura, ao diâmetro do caule e à clorofila foliar. Após 210 dias, as plantas foram coletadas e avaliadas para peso fresco e seco da parte área e do sistema radicular e o material de solo foi avaliado quanto à fertilidade e atividade microbiana pelo carbono do CO2 liberado. A incorporação de resíduo orgânico ao material de solo degradado afetou positivamente a fertilidade deste e a atividade microbiana. As doses de fósforo aplicadas influenciaram o comportamento de Ca, SB, H+Al e CTC e, quando aplicadas na ausência de resíduo orgânico, promoveu incrementos significativos e lineares nos valores da acidez potencial, mostrando a importância da presença do resíduo orgânico. O crescimento inicial do Dipteryx alata foi favorecido pelo cultivo protegido, pela incorporação de resíduo orgânico e pela adição de fósforo ao solo. Pode-se concluir ainda que há boa perspectiva para deposição deste resíduo sobre o material de solo degradado, embora estudos em condições de campo sejam necessários.
Organic residue and phosphorus as conditioners of degraded soil and effects on the initial growth of Dipteryx alata Vog.
Keywords: vegetation re-establishment; macrophyte; soil fertility; soil microbiology; revegetação; macrófitas; fertilidade do solo; microbiologia do solo